Perioperative Management for Patients with Hereditary Angioedema - Anesu H. Williams D.H.Sc., M.P.A. (Allergy & Rhinology, 2015)
Hereditary angioedema (HAE) is a rare autosomal dominant disease that results from mutations in the C1-esterase inhibitor (C1-INH) gene. HAE is characterized by recurrent episodes of angioedema of the skin (face, extremities, genitalia, trunk), the gastrointestinal tract, and respiratory tract. Symptoms experienced can be debilitating, may impact quality of life, and can be life threatening. Preventing attacks particularly for patients undergoing procedures is critical. Patients with HAE may now treat acute attacks or prevent attacks with medications that have recently become available in the United States; however, these same medications can be used for perioperative management for patients undergoing medical, surgical, and dental procedures. Periprocedural planning is important for patients to reduce the incidence of acute attacks. Education is critical and increasing awareness of short-term prophylaxis options will allow providers to develop an appropriate action plan for their patients. The goal of this review is to increase awareness for HAE treating physicians, surgeons, anesthesia, and emergency room physicians by examining the available treatment options, researching the literature, and summarizing available data for periprocedural management. The availability of treatment options has increased over the past few years, expanding options for physicians and patients living with HAE and improve safety during the perioperative period and at the time of other procedures.